The role of research in shaping the educational field in Chile. Perspectives, influences and omissions (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2020)
In the last decades, capitalist globalization has triggered profound transformations, favoring the emergence of new actors and modes of education governance, and influence process. These changes have promoted an extensive literature focused in the role of social movements in the production of the field, but other actors -such as academics, experts and agents who act as knowledge intermediaries- have been scarcely analyzed. In this sense, the paper develops a conceptual model to analyze the factors and actors that contribute to the configuration of the educational field in Chile; and particularly, it focuses on the role carried out by academics and educational research in this process. Finally, the conclusions point out to the importance of analyzing the mechanisms that favor the influence of scholars and educational research in the production of educational policies and identify four relevant future lines of research.Keywords: Educational field. Chile. Research. Knowledge. Evidence-based policy.